Der Gegenstand des Feststellungsverfahrens Rechtsverhältnis und rechtliches Interesse bei Feststellungsstreitigkeiten vor Zivil- und Arbeitsgerichten - Jacobs, Matthias (Mohr Siebeck, 2005)
Matthias Jacobs examines the admissibility requirements of an action for a declaratory judgment in civil proceedings and their historical and teleological basis. He reveals the weaknesses in the traditional dogmatics, reappraises the action for a declaratory judgments loss of substance in substantive law and attempts to outline and delimit the legal protection area in Section 256 Paragraph 1 of the Code of Civil Procedures more precisely than before by connecting it to substantive law.
PublicationDate: 20200518
Keywords: Zivilverfahrensrecht -- ZPO -- Augustus -- Feststellungsverfahren -- Liturgische Poesie -- Bürgerliches Recht -- Zivilverfahrensrecht, Insolvenzrecht